Review of the cicada genus Mogannia Amyot & Serville from China, with descriptions of three new species (Hemiptera: Cicadidae) - Chen, Xiao; Yang, Mingsheng; Wei, Cong (Zootaxa, 2012)
The species of Mogannia Amyot & Serville from China are reviewed. Twelve species are illustrated or photographed, including nine known species and three new species. Information on the biology and distribution are provided, and a key to all species of Mogannia from China is presented. The variation of some species of the genus Mogannia and the systematic status of the tribe Cicadatrini Distant are discussed. Morphological attributes for Mogannia indicate that it is allied to the subfamily Cicadettinae, however, we tentatively retain it in the subfamily Cicadinae, as other related genera of the Cicadatrini also need to be addressed.